2003
DOI: 10.3233/ip-2003-0023
|View full text |Cite
|
Sign up to set email alerts
|

E-voting in Europe: Divergent democratic practice

Abstract: Recent technological developments have opened up the possibility of electronic voting and this clearly provides some opportunities and threats. On the one hand, the new technology may help to make voting more cost effective and more convenient for the voter and may even increase voter turnout. On the other, e-voting may introduce new risks and affect electoral values, such as the secrecy of the vote and the place of voting as an observable institution in modern democracies.At present various countries and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 13 publications
1
21
0
1
Order By: Relevance
“…Therefore, there is a need to explore the factors including attitudes and beliefs that influence that kind of interaction. Previous studies have indicated the significant role of attitudes when discussing e-voting as a new change in social communities [14] [15]. This study presented a different way of studying attitudes in relation to the e-voting context by focusing on a citizen-centric approach in addressing the impact of voters' attitudes on their intentions to use an evoting system.…”
Section: E-government Adoption Modelmentioning
confidence: 97%
“…Therefore, there is a need to explore the factors including attitudes and beliefs that influence that kind of interaction. Previous studies have indicated the significant role of attitudes when discussing e-voting as a new change in social communities [14] [15]. This study presented a different way of studying attitudes in relation to the e-voting context by focusing on a citizen-centric approach in addressing the impact of voters' attitudes on their intentions to use an evoting system.…”
Section: E-government Adoption Modelmentioning
confidence: 97%
“…(2005) Aikens (1998), Albrecht (2006), Bekkers (2004), Dahlberg (2001), Huang (1998), Jensen (2003b, Lourenco and Costa (2006), Luhrs et al (2003), Macintosh et al (2003), Pejout (2004), Siapera (2005), Snider (2003, Whyte and Macintosh (2001) e-Inclusion-examination of the availability of eParticipation to citizens across social boundaries (digital divide), particularly in relation to access to technology (and the possibilities engendered by technology) Ainsworth, Hardy, and Harley (2005), Albrecht (2006), Belanger and Carter (2006), Dutta-Bergman (2005) Koch (2005), Rosenblatt (1999), Westholm (2002) e-Rulemaking-participation in the process that is used to create or promulgate, regulations Carlitz and Gunn (2002) e-Voting-participation through voting over the Internet or by other electronic means Drechsler and Madise (2002), Gibson (2001), Kenski (2005), Kosmopoulos (2004), Oravec (2005), Padget (2005), Prosser, Kofler, and Krimmer (2003), Schaupp and Lemuria (2005), Smith and Clark (2005), Svensson and Leenes (2003), Xenakis and Macintosh (2005) Though the range of theories in the literature sample is eclectic, a well-used philosophical background to the eParticipation discussion is Habermas' conception of the public sphere, whilst various democracy theories (often expressed as democracy models) form a common theoretical focus.…”
Section: Article In Pressmentioning
confidence: 98%
“…Discovery of technology solutions (e.g., software architectures) to participatory computer systems Paralic and Sabol (2001), Paralic, Sabol, and Mach (2002), Paralic, Sabol, and Mach (2003) Information systems Technology diffusion (Rogers, 1995) Integrating ICTs with governmental policies and services Chadwick (2003), Chadwick and May (2003), Schaupp and Lemuria (2005) Technology adoption (Markus & Robey, 1988) Beliefs, attitudes, opportunities, and threats to adoption of technology Schaupp and Lemuria (2005), Svensson and Leenes (2003) Social cognitive theory (Hemingway, 1998) Reconciles human action and human agency to explain how citizens and governments impact systems development Whyte and Macintosh (2003) Actor network theory (Latour, 2005) Influence of deliberative democracy models on democratic behavior Gro¨nlund (2003aGro¨nlund ( , 2003b Social and political philosophy Kant's doctrine of right and his theory of the state (Kant, 1996) The principle of publicity in the realm of law or the state that is instantiated by the participation of citizens through discussion and decision-making Gimmler (2001) Habermas public sphere (1984,1996) Philosophical background of participation, asks how the Internet may alter the practice of politics Ainsworth et al (2005), Albrecht (2006), Dahlberg (2001), DiMaggio, Hargittai, Neuman, andRobinson (2001), Gimmler (2001), Howard (2005), Jensen (2003b, Lourenco and Costa (2006), Pejout (2004), Polat (2005), Siapera (2005) Philosophy of information (Dretske, 1981) A critical investigation of the conceptual nature and basic impact of information including its dynamics and utilization in...…”
Section: Communicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…During the late 1990s and early 2000s a host of European countries outlined plans to introduce e-voting broadly understood (Kersting and Baldersheim 2004;Trechsel and Mendez 2005). A paper in 2003 listed 13 Western European countries experimenting with e-voting (Svensson and Leenes 2003) while a database on e-voting identifies 14 European countries with advanced e-voting programmes. 1 Most of these programmes were initiated in the early 2000s yet almost a decade later very few countries have conducted binding elections via the Internet.…”
Section: Framework Of Analysismentioning
confidence: 99%